A Performance Evaluation Study of a smart lawn Mower for Improving Cutting Efficiency and Optimising Operation Time - Shuib, Siti Khalijah; Mohd Zainuddin, Khadijah; Ibrahim, Mohamad Shahril (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aimed to assess the performance of a smart lawn mower designed to boost the efficiency of operational activities and optimize the landscape maintenance period in an educational campus environment. Background Problems: Manual grass-cutting activities, which are still common in educational institutions in Malaysia, are time-consuming, require significant manpower, and result in an inconsistent cutting style. Novelty: This study presents an automated, smart lawn mower that uses an electric driving system with central control to increase operational productivity and decrease reliance on human labor. Research Methods: The study uses a quantitative experimental comparison approach between the smart lawn mower and the manual method on a 2,000 square feet test site. The evaluated parameters are operational time (minutes) and cutting rate (area cut/time). The savings and effectiveness were analyzed using a percentage increase method. Finding/Results: The results showed that the smart lawn mower reduced operational time by 50% (from 40 minutes to 20 minutes) and increased the cutting rate by 100% compared to the manual method. Conclusion: The automated system significantly enhances time efficiency and productivity. It also supports green campus initiatives through efficient technology and user-friendly maintenance. This research demonstrates the potential of integrating automated technology into landscape maintenance as a modern, sustainable solution and lays the groundwork for future IoT-based smart lawn mower systems.